História da formação de professores de matemática do ensino primário em Minas Gerais: estudos a partir do acervo de Alda Lodi (1927 a 1950) - Diogo Alves de Faria Reis (2014)
The research reported in this thesis investigated educational practices and proposals for the training of teachers in the elementary years of school education with regard to Mathematics, in Belo Horizonte, for the period 1927 to 1950, from the Alda Lodi Personal Archive (APAL). We seek to understand Alda Lodis training during the period in which she was at Teacher's College; which teaching concepts were adopted by her; and what strategies the teacher utilized to teach Methodology of Arithmetic in the School of Improvement and in the School Administration Course for student teachers. We seek to understand through the analysis of APAL documents, the training and performance of teacher Alda Lodi in the training of elementary school teachers in Minas Gerais. Among the various possible paths to achieve the outlined goals, were inspired by two methodological theories: Paradigm of Evidence by Carlo Ginzburg, and Depth Hermeneutics by John B. Thompson. Considering that the subject is specific to "teaching to teach" Mathematics to elementary school teachers, the work falls in the field of History of Mathematics Education. We chose to present the report of our research in multipaper format, building the thesis through four independent studies, but interrelated. In the first study, we mention the practices and proposals of the training of teachers for elementary school education from the Alda Lodi Personal Archive, narrating our search path. In the second study, we undertook the description of APAL and praised Alda Lodi; we also addressed the methodological inspiration based in our research. The third study consists of the submission of a formal analysis of Alda Lodis student notebooks that integrates the collection, on the basis of the Thompson theory. The last study includes the results of our analysis of the APAL documents relating to speeches and adjustments that we perceive through the actions of Alda Lodi in teaching teachers to teach arithmetic according to the new school prospects in Minas Gerais.